2019
DOI: 10.1152/japplphysiol.00490.2019
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological attenuation of group III/IV muscle afferents improves endurance performance when oxygen delivery to locomotor muscles is preserved

Abstract: We sought to investigate the role of group III/IV muscle afferents in limiting endurance exercise performance, independently of their role in optimizing locomotor muscle O2 delivery. While breathing 100% O2 to ensure a similar arterial O2 content ([Formula: see text]) in both trials, eight male cyclists performed 5-km time trials under control conditions (HCTRL) and with lumbar intrathecal fentanyl (HFENT) impairing neural feedback from the lower limbs. After each time trial, common femoral artery blood flow (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 51 publications
4
27
0
Order By: Relevance
“…Further, it has been recognized that these impairments in muscular performance are likely a consequence of diminished oxygen delivery (Hureau et al . 2019). Therefore, the detrimental influence of blood flow occlusion on muscle recruitment and force production demonstrated in this study may be directly related to attainment of a STL, which is effectively raised and perhaps not reached, in studies employing group III/IV afferent blockades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it has been recognized that these impairments in muscular performance are likely a consequence of diminished oxygen delivery (Hureau et al . 2019). Therefore, the detrimental influence of blood flow occlusion on muscle recruitment and force production demonstrated in this study may be directly related to attainment of a STL, which is effectively raised and perhaps not reached, in studies employing group III/IV afferent blockades.…”
Section: Discussionmentioning
confidence: 99%
“…While, pharmacological blockade allows the role of group III/IV afferents to be elucidated without compromising skeletal muscle oxygen delivery (Hureau et al . 2019), these interventions also obfuscate the observation of sensory input‐induced restrictions to CMD (i.e. reduced motor unit activation).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Black et al 24 measured changes in a F I G U R E 2 Relationship between time to post-exercise assessment and reduction in knee extensor maximum voluntary contraction (MVC; A), voluntary activation (VA; B) and peak twitch force (P tw ; C) as a percentage of pre-exercise. 17,22,23,31,61,[66][67][68][69][70][71][72][73][74][75][76] The R 2 is derived from the logarithmic slope presented on each graph range of metabolic variables including PCr, lactate, K + , ATP, pH and glycogen (variables which are linked with the reduction in P tw 36 ), and found no difference in the change in any variable when exercise was performed at three different intensities within the severe domain (65%, 75% and 85% of work-rate difference between gas exchange threshold and VO 2max , in which task failure occurred from 2.2 to 13.9 minutes), although peak twitch was not measured in the study. It has been proposed that a consistent magnitude of end-exercise alterations in metabolic variables (and thus P tw ) could exist due to a task specific "individual critical threshold" of peripheral alterations in response to severe intensity locomotor exercise, beyond which the degree of associated sensory perceptions would not be tolerable.…”
Section: Muscle Force Generating Capacity Voluntary Activation Andmentioning
confidence: 99%
“…In addition to measuring the specific effects on group III/ IV afferent feedback on motor cortical and α-motoneuronal excitability discussed above, a plethora of studies have assessed the effects of group III/IV afferent feedback on neuromuscular function through more global responses such as EMG and P tw . 17,61,72,73,85 These studies have demonstrated that group III/IV afferents constrain motoneuronal output (estimated through EMG) to active skeletal muscle, thereby limiting exercise-induced intramuscular alterations. For example, Blain et al 73 had participants perform a 5 km cycling time trial under control conditions and with fentanyl induced impairment in afferent feedback.…”
Section: Motor Cortical Outputmentioning
confidence: 99%
“…Furthermore, partial blockade of group III and IV muscle afferents at the spinal level results in the attenuation of perceived fatigue, and increases central motor drive (Amann et al 2009 ). Based on these findings, it is suggested that the increased activation of group III and IV afferents inhibits central motor drive and the ability to recruit motor units (Amann et al 2011 ; Hureau et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%